Bacillus cabrialesii BH5 Protects Tomato Plants Against Botrytis cinerea by Production of Specific Antifungal Compounds - Zhou, Lu; Song, Chunxu; Muñoz, Claudia Y.; Kuipers, Oscar P. (Frontiers in Microbiology, 2021)
Abstract: The grey mould caused by the phytopathogen Botrytis cinerea presents a threat to global food security. For the biological regulation of several plant diseases, Bacillus species have been extensively studied. In this work we explore the ability of a bacterial strain, Bacillus cabrialesii BH5, that was isolated from tomato rhizosphere soil, to control the fungal pathogen Botrytis cinerea. Strain B. cabrialesii BH5 showed a strong antifungal activity against B. cinerea. A compound was isolated and identified as a cyclic lipopeptide (CLP) of the fengycin family by high-performance liquid chromatography (HPLC) and tandem mass spectrometry (ESI-MS/MS), that we named fengycin H. Analyses using propidium iodide (PI) staining revealed that fengycin H was responsible for cell wall integrity defects and finally the death of B. cinerea hyphal cells. Moreover, root inoculation of tomato seedlings with BH5 effectively promoted the growth of tomato plants. Transcription analysis revealed that both BH5 and fengycin H stimulate induced systemic resistance (ISR) of tomato plants via the jasmonic acid signaling pathway and provide a strong biocontrol effect in vivo. Therefore, the strain BH5 and fengycin H are very promising candidates for biological control of B. cinerea and the associated grey mould.